Enhanced Recovery After Surgery (ERAS) Eliminates Racial Disparities in Postoperative Length of Stay After Colorectal Surgery. Issue 6 (December 2018) - Wahl, Tyler S.; Goss, Lauren E.; Morris, Melanie S.; Gullick, Allison A.; Richman, Joshua S.; Kennedy, Gregory D.; Cannon, Jamie A.; Vickers, Selwyn M.; Knight, Sara J.; Simmons, Jeffrey W.; Chu, Daniel I.
Abstract : Objective: To investigate the effects of enhanced recovery after surgery (ERAS) on racial disparities in postoperative length of stay (pLOS) after colorectal surgery. Background: Racial disparities in surgical outcomes exist. We hypothesized that ERAS would reduce disparities in pLOS between black and white patients. Methods: Patients undergoing ERAS in 2015 were 1:1 matched by race/ethnicity, age, sex, and procedure to a pre-ERAS group from 2010 to 2014. After stratification by race/ethnicity, expected pLOS was calculated using the American College of Surgeons National Surgical Quality Improvement Project Risk Calculator. Primary outcome was the observed pLOS and observed-to-expected difference in pLOS. Secondary outcomes were National Surgical Quality Improvement Project postoperative complications including 30-day readmissions and mortality. Adjusted sensitivity analyses on pLOS were also performed. Results: Of 420 patients (210 ERAS and 210 pre-ERAS) examined, 28.3% were black. Black and white patients were similar in age, body mass index, sex, American Anesthesia Association class, and minimally invasive approaches. Within the pre-ERAS group, black patients stayed a mean of 2.7 days longer than expected compared with white patients ( P < 0.05). Overall, ERAS patients had a significantly shorter pLOS (5.7 vs 8 days) and observed-to-expected difference (−0.7 vs 1.4 days) compared with pre-ERAS patients ( P < 0.01). In the ERAS group, disparities in pLOS were reduced with no differences in readmissions or mortality between black and white patients. On sensitivity analyses, race/ethnicity remained a significant predictor of pLOS among pre-ERAS patients, but not for ERAS patients. Conclusions: ERAS eliminated racial differences in pLOS between black and white patients undergoing colorectal surgery. Reduced pLOS occurred without increases in mortality, readmissions, and most postoperative complications. ERAS may provide a practical approach to reducing disparities in surgical outcomes. Abstract : Supplemental Digital Content is available in the text